Pest control for Tetragonisca Angustula: Design, prototyping and evaluation - León-Bravo, Wilmer Esneyder
The increasing number of beekeepers dedicated to native stingless bees in Colombia has led to the need for developing products that help overcome the challenges encountered in their care. One of these challenges is the presence of invaders and pests that affect the hives. Therefore, it is imperative to design, prototype, and evaluate a pest control system for the Tetragonisca Angustula species using innovative technologies such as 3D printing, which offers the advantage of manufacturing customized parts tailored to the specific needs of the species. During the design process, it is essential to consider aspects such as dimensions, filament type, common pests and invaders, as well as the species’ characteristics. These factors contribute to the initial product sketch. Once the parts that make up the pest control prototype are determined, the model is designed using software like SketchUp, followed by slicing in the CURA program and printing the pieces. Subsequently, the installation is carried out in rational or intelligent boxes in the INPA and AF models to evaluate its functionality. At the end of the data recording and observation period, it has been confirmed that the designed device was effective in controlling pests such as the humpback fly, ants, robber bees, toads, and lizards.